Investigating the benefits of a mature e-government to business (G2B) system in South Africa - Dhlamini, Ntokozo (My University, 2020)
Purpose – The purpose of this study was to test the relationships between the dimensions that are predicted to contribute to the success of mature e-government systems. The measurement of e-government success is still not well understood by both practitioners and researchers, and this study therefore aimed to provide empirical validation for the success of mature e-government systems, with particular focus on private companies in South Africa. Mature e-government systems are predicted to contribute to effective and efficient governments that enable the sharing of information, and the delivery of seamless, integrated e-government services. This has the potential to reduce the administrative burden on companies, and improve the transparency and accountability in e-government systems and government officials. Design/methodology/approach – A quantitative survey design was used and an online survey questionnaire was sent to companies that were registered and using the Central Supplier Database (CSD) system, focusing on small and medium enterprises (SMEs) in South Africa. Findings – All the predicted relationships between all the constructs were supported by the results of this study, except for “service quality” which had to be dropped from the research model after failing validity scrutiny. The findings also revealed that SME companies perceive public value from all of the dimensions of the “net benefits” measure, for all the elements that were derived from the Public Value theory, namely, efficiency, effectiveness and improved democracy. Originality/value – The study attempted to add to the body of knowledge in the Information Systems discipline by validating the extended DeLone and McLean IS Success model within the less explored aspects of the e-government discipline, involving the evaluation of a mature e-government system utilized by private companies in a developing country such as South Africa, with particular emphasis on reducing administrative burden on these companies. This study integrated constructs mainly from the DeLone and McLean IS Success model with elements from the Public Value theory, namely efficiency, effectiveness and improved democracy, to cater for the unique aspects of e-government systems. Practical implications – This research may assist government officials, IS practitioners and academics understand the potential success of e-governments within the South African context and also to understand the factors that might influence the success of mature e-government systems. It may also help guide policy makers towards making the most appropriate decisions when implementing such systems and initiating other e-government projects
A research report submitted in partial fulfilment of the requirements for a degree of Masters in Commerce (Information Systems) at the University of Witwatersrand, Johannesburg, Faculty of Commerce, Law and Management, 2020